Immunochemotherapy achieved a complete response for metastatic adenocarcinoma of unknown primary based on gene expression profiling: a case report and review of the literature - Sheng, Jin; Pan, Hongming; Han, Weidong (Frontiers in Immunology, 2023)
Background: Cancer of unknown primary (CUP) is a malignant and aggressive tumor whose primary origin is still unknown despite thorough evaluation. CUP can be life-threatening with a median overall survival of less than 1 year based on empirical chemotherapy. Gene detection technology advances the driver gene detection of malignant tumors and the appropriate precise therapy. Immunotherapy has ushered in a new era in cancer therapy, changing the way advanced tumors, including CUP, are treated. Combined with comprehensive clinical and pathological investigations, molecular analysis of the original tissue and detection of potential driver mutations may provide therapeutic recommendations for CUP. Case Presentation: A 52-year-old female was admitted to hospital for dull abdominal pain, with peripancreatic lesions below the caudate lobe of the liver and posterior peritoneal lymph nodes enlargement. Conventional biopsy under endoscopic ultrasonography and laparoscopic biopsy both revealed poorly differentiated adenocarcinoma based on immunohistochemical series. To help identify tumor origin and molecular characteristics, 90-gene expression assay, tumor gene expression profiling with Next-generation sequencing (NGS) method and Immunohistochemical expression of PD-L1 were employed. Although no gastroesophageal lesions discovered by gastroenteroscopy, the 90-gene expression assay yielded a similarity score and prompted the most likely primary site was gastric/esophagus cancer. NGS revealed high TMB (19.3mutations/Mb) but no druggable driver genes identified. The Dako PD-L1 22C3 assay IHC assay for PD-L1 expression revealed a tumor proportion score (TPS) of 35%. Given the presence of negative predictive biomarkers (APC c.646C>T mutation at exon 7 and JAK1 c.425del mutation at exon5) for immunotherapy, the patient received immunochemotherapy instead of immunotherapy alone. She was successfully treated with nivolumab plus carboplatin and albumin-bound nanoparticle paclitaxel for six cycles and nivolumab maintenance, which achieved a complete response (CR) maintained for 2 years without severe adverse events. Conclusions: This case highlights the value of multidisciplinary diagnosis and individual precision treatment in CUP. Further investigation is needed as an individualized treatment approach combining immunotherapy and chemotherapy based on tumor molecular characteristics and immunotherapy predictors is expected to improve the outcome of CUP therapy.